UK childhood exposures to pesticides 2004–2007: a TOXBASE toxicovigilance study. Issue 6 (8th January 2009) - Adams, R D; Lupton, D; Good, A M; Bateman, D N
Abstract : Objective: There are no systematic methods for toxicovigilance of non-medicinal products in the UK. This is particularly relevant for pesticides, where there is significant public concern about potential adverse effects. This study describes a prospective toxicovigilance scheme based on follow-up of enquiries to the National Poisons Information Service (NPIS) through its online poisons information system TOXBASE. These enquiries reflect acute exposures and the patterns of acute illness that result. Results: A total of 10 061 pesticide-related enquiries were identified. After follow-up, data were gathered on 2364 suspected exposures, of which 1162 involved children. After exclusions, 1147 exposures are reported here. No deaths were reported and only 37 children were admitted to hospital. The majority were considered to have either minimal or no features (925, 80.6%). Symptoms for 38 children were unknown. Symptoms reported in the other 184 children included nausea or vomiting (58), eye irritation, pain or conjunctivitis (29), skin irritation (28), abdominal pain (24), mouth or throat irritation (18) and diarrhoea (15). Where age was recorded, 60.5% (680) of children involved in suspected pesticide exposures were aged 2 years or less. The most common scenario for acute accidental exposure to pesticide in children was exposure after application (329, 28.7%) or due to poor storage (228, 19.9%). Conclusions: Areas of potential concern identified included storage, access of young children to "laid" baits and pesticides, and exposures as a result of medication errors, with liquid head lice preparations being confused with other medicines. Use of NPIS systems provides a potentially useful method of toxicovigilance.